Mitigating stress effects during transportation of matrinxã(Brycon amazonicus Günther, 1869; Characidae) through the application of calcium sulfate - Bendhack, F. [UNESP]; Urbinati, E. C. [UNESP] (Hindawi, 2009)
This study verified the effects of CaSO4 on physiological responses of the tropical fish matrinxãBrycon amazonicus(200.2 ± 51.1 g) in water containing CaSO4 after a 4-h transportation at concentrations of: 0, 75, 150, and 300 mg L-1. Blood samples were collected prior to transportation (initial levels), immediately after packaging, at arrival, and 24 h and 96 h after transportation (recovery). Cortisol levels increased after ackaging (118.2 ± 14.2 ng ml-1), and decreased slightly after transportation in water containing CaSO4 (106.8 ± 14.1), but remained higher than initial levels (21.0 ± 2.6 ng ml)1). Fish kept at 150 mg L-1 CaSO4 reached the pre-transportation levels at 24 h of recovery. Blood glucose increased after transportation in all treatments (8.2 ± 0.2 mmol L-1) and declined after full recovery to values below initial levels (4.8 ± 0.1 mmol L-1). Chloride levels did not change in CaSO4 treatments; serum sodium concentrations decreased after packaging and after transportation. Serum calcium levels did not differ among treatments, but decreased after packaging and increased at 96 h of recovery. Hematocrit and the number of red blood cells were higher in all treatments after packaging and arrival, except in fish exposed to 300 mg L-1 CaSO4. Mean corpuscular volume increased in 75 mg L-1 CaSO4, which reached the higher VCM after transportation. Hemoglobin levels increased only after transportation, regardless of calcium sulfate levels. Handling before transportation and transportation itself were both stressful to fish; calcium sulfate at concentrations tested in the present work had a moderate influence in the reduction of stress responses. © 2009 Blackwell Verlag, Berlin.
Keywords: Brycon; Characidae